Self-Regulated Learning on Santri: The Personality Type, Spiritual Intelligence, and Social Support - Subchi, Imam; Badranaya, Djaka; Bachmid, Achmad; Nufus, Amelia Zakiyyatun; Muhammadiyah, Hilmi (Universitas Islam Negeri Raden Intan Lampung, 2023)
In learning, students should possess the capability to manage their learning effectively to achieve optimal outcomes. Consequently, self-regulated learning becomes crucial for students, encompassing not only general subjects but also religious studies. This research investigates the influence of Personality Type, Spiritual Intelligence, and Social Support on Self-Regulated Learning at Al-Nahdlah Islamic Boarding School. Employing a quantitative method, this study adopts a correlation approach. The sampling technique utilized is probability sampling, specifically stratified random sampling. From 116 students at Al-Nahdlah Islamic Boarding School, a sample of 56 was chosen. For validation, this research employs Confirmatory Factor Analysis (CFA) using the Lisrel 8.7 software. Subsequent data analysis was conducted using multiple regression analysis in the SPSS software. Findings indicate a significant influence of Personality Type, Spiritual Intelligence, and Social Support on Self-Regulated Learning among Al-Nahdlah Islamic Boarding School students. The combined contribution of these independent variables to Self-Regulated Learning is 29.0%, leaving 71.0% influenced by other factors. Thus, Personality Type, Spiritual Intelligence, and Social Support significantly impact students' self-regulated learning capabilities. By enhancing students' spiritual intelligence, understanding their personality types, and strengthening their social support networks, institutions can better foster self-regulated learning capabilities, leading to improved academic outcomes and holistic student development.